Konsep Zuhud Pada Ajaran Tasawuf Dalam Kehidupan Santri Pada Pondok Pesantren - Ratna Dewi (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2021)
This article discussed about the concept of zuhud in the teachings of Sufism in the lives of students at Islamic boarding schools through recitation using the book